Higher Education Institution Research Dissemination and Utilization through the Lens of Community Engagement - Clores, Vincent M. (UI Scholars Hub, 2021)
Using community involvement as a lens, this study analyzed the amount of distribution and utilization of a public higher education institution's research outputs in Bicol, Philippines. The Diffusion and Dissemination Theory alongside the use of Knowledge For health (K4Health) of the United States Agency for. International Development (USAID) Model served as the theoretical and conceptual underpinnings of this study that facilitated the analysis of research produced by the institution, its dissemination, the enablers, and barriers, and until utilization. The case study design was used to portray an in-depth analysis of the institution’s situation from research output generation to the enablers and barriers to research utilization. The analysis of graduate student and faculty research revealed a predominance of quantitative descriptive study on the issue of “research in aid of policies.” Documentary evidence on research outputs utilized in policies, programs, and projects is minimal. For the faculty, the enablers on research utilization are promotions and incentives while for the graduate students it is a provision of better library services and research resources. The faculty considered personal and professional issues as barriers while the graduate students cited accessibility of resources, access policies, and professional/work-related issues. Overall, the utilization of research in the institution characterizes Conceptual Research Utilization (CRU) only. In conclusion, the overall dissemination and utilization of research are still beset with leadership, management, access to dissemination tools, research resources, and researcher motivation issues. Due to insufficient attention being placed on research applications to capacitate and empower the community, the approach contributed to low research output utilization. It is suggested that the proposed action plan based on the findings of this study be implemented.